Reorienting Islamic Education in Aceh: Paradigm and Strategies of Dayah Leaders in the Last Two Decades - Silahuddin, Silahuddin; Wirianto, Dicky; Riza, Muhammad; Zalnur, Muhammad (AT-TA'LIM, 2023)
This article aims to shed light on Abu's (a Dayah leader in Aceh) paradigm and strategy in reorienting Islamic education inside the dayah educational framework in the last two decades. Even now, the Acehnese people's socio-religious life still accepts and includes the traditional Islamic educational institution known as dayah. However, Dayah must adapt to the dynamics of the changing times to ensure its graduates to participate more fully in society. The Dayah in West-South and East-North coasts of Aceh are the subjects of this qualitative study using a multi-site case study. They are Dayah Asasul Islamiyah in East Aceh, Dayah Madinatuddiniyah Nurul Huda in North Aceh, Dayah Madinatuddiniyah Darul 'Ulumiddin in Southwest Aceh, and Dayah Darussalam Labuhan Haji in South Aceh. The research data was gathered through purposeful-snowballing in-depth interviewing techniques with a variety of informants, including Abu as the dayah's leader. After that, the data is processed using interactive analytic procedures, which include condensing, presenting, and concluding. According to the study's findings, Aceh's dayah leaders' (Abu) paradigm has shifted from being exclusive and orthodox to being inclusive and flexible during the dayah's current period of development. The Mua'dalah programme and the higher education programme Ma'had Aly were both implemented as part of Abu's strategy to reorient Islamic education in dayah, as well as the training of human resources to become educators,